Sistemática molecular de Thaptomys Thomas, 1916 (Rodentia, Cricetidae) - Cordeiro, Juçara Albina da Silva Gomes (2008)
Thaptomys is a monotypic genus. Thaptomys nigrita is only species recognized to the genus to the moment, although the taxonomic history of genus reveals more than one species has been described in the literature. Currently, there are four scenarios presented in taxonomic literature for the genus: 1) A single species, without subspecies, with wide geographical distribution, 2) One species with two subspecies, being Thaptomys nigrita nigrita distributed between southern of Bahia to northern of Santa Catarina and Thaptomys nigrita subterraneus distributed south of São Paulo to the north of Rio Grande do Sul, including eastern of Paraguay and northeastern of Argentina; 3) Two species with karyotype distinction, being Thaptomys sp. restricted to the south of Bahia with 2n = 50 and Thaptomys nigrita occurring in the rest of the genus distribution with 2n = 52, 4) Two species with morphological differentiation and one variant form, being Thaptomys sp. found in southern of Bahia and Thaptomys nigrita represented by the individuals found in the rest of the distribution of the genus, and a variant form found in Paraná. Thus, the objective of this study was to evaluate the four scenarios to the genus Thaptomys using molecular markers, and to test the existence of more than one taxonomic unit for the genus, from the study of 833 bp of nuclear gene cytochrome b (cit b). For this, we used population genetics analyzes, phylogenetic analyzes and analyzes of molecular variation (AMOVA). Our results revealed that the populations of the ends of the distribution are balanced demographic and population center of the distribution are expanding population. The time since the expansion reveal that the northern populations expanded to southward and southern populations expanded to northward. Phylogenetic analyzes and AMOVA reveal the existence of four evolutionarily significant units. Thus, we propose the existence of four taxonomic units for the genus Thaptomys: Thaptomys sp1, with 2n = 50 to the south of Bahia, Thaptomys nigrita to Espírito Santo, Minas Gerais, Rio de Janeiro and north of São Paulo, with 2n = 52; Thaptomys sp 2 to the center and east of São Paulo and Thaptomys subterraneus to south of São Paulo to Rio Grande do Sul, including northeastern to Argentina